2017
DOI: 10.1097/nna.0000000000000467
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Informatics Competency Assessment for the Nurse Leader

Abstract: This work can advance nursing practice to move beyond "on-the-job informatics training" to a more competency-based model of nursing informatics education and practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 9 publications
1
74
0
6
Order By: Relevance
“…Sufficient training and participation might help leaders' to adapt to complex HIT implementation [56], and help them to adopt the required roles and support the success of HIT implementation by maintaining a positive attitude towards HIT [50]. Some pioneer organisations have already implemented the positions of chief medical informatics officers and chief nursing informatics officers [57], who are specialists in clinical work, management and information technology [20,21]. The recent results of Fenton et al [57] highlight the requirement for and subsequent development of a doctorate in health informatics (DHI).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sufficient training and participation might help leaders' to adapt to complex HIT implementation [56], and help them to adopt the required roles and support the success of HIT implementation by maintaining a positive attitude towards HIT [50]. Some pioneer organisations have already implemented the positions of chief medical informatics officers and chief nursing informatics officers [57], who are specialists in clinical work, management and information technology [20,21]. The recent results of Fenton et al [57] highlight the requirement for and subsequent development of a doctorate in health informatics (DHI).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the changing environment and advances in healthcare technology, the roles of healthcare leaders have expanded [19]. Traditionally, it has been part of the healthcare leader's role to have competency in clinical health services and management [19], but now, leaders must also possess knowledge of technologies related to health information [20,21]. Because leaders can have a positive or negative impact on HIT implementation [6,12,15], more research is needed concerning the role of leaders in HIT implementation [18,22,23], taking all leadership levels into account [22,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, NI are suggested to be core competencies instead of an isolated set of skills in nursing (Abdrbo 2015;Kleib and Nagle 2018;Sipes et al 2017). Informatics competency requirements are set for different roles and all levels of nurses (nurse administrators, nurse researchers, nurse teachers and practicing nurses) (Collins et al 2017;Egbert et al 2018;Grobe 1989;Kannry et al 2016;Skiba 2016;Strudwick et al 2019) and across different levels in health systems, ranging from service providers to national-level strategic decision makers (Whittaker et al 2015). However, a systematic and formal approach to the implementation of NI in nursing education is still lacking in some countries (Cummings et al 2015;Egbert et al 2018), and research has shown that graduate nurses are inadequately prepared in NI when entering practice (Shin et al 2018) and that more NI training is needed at postgraduate levels in nursing (Choi et al 2013;Kupferschmid et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…(15) In the case of the present study, the participants did not consider the use of technological systems for capturing data and assessments to be a relevant APN competency, unlike other studies that showed the importance and relevance of this aspect among the core competencies. (20,21) Informatics and knowledge of technological systems should be core competencies in professional nursing practices, since the development of these competencies promotes, improves and facilitates collaboration and integration with other professions, besides other benefits. (20,21) Finally, the implementation of APN requires a definition of the core competencies for the training of these nurses, in addition to knowledge on the experiences of other countries.…”
Section: Discussionmentioning
confidence: 99%
“…(20,21) Informatics and knowledge of technological systems should be core competencies in professional nursing practices, since the development of these competencies promotes, improves and facilitates collaboration and integration with other professions, besides other benefits. (20,21) Finally, the implementation of APN requires a definition of the core competencies for the training of these nurses, in addition to knowledge on the experiences of other countries. Considering that most of the competencies examined in this study were considered relevant by the participants, it is possible to use them once a consensus has been reached and they are contextualized in each country.…”
Section: Discussionmentioning
confidence: 99%